Riesgos de incendios en los Talleres de la Asociación de Artesanos Pirotécnicos San José del cantón Chimbo y su reducción de riesgo mediante el sistema de la Universidad Estatal de Bolívar periodo 2020 - Mora Maya, Richard Iván (2021)
At the time of starting fires in the craft pyrotechnics manufacturing workshops in the canton of San José de Chimbo, due to the ignorance of safety regulations, the need arises to reduce the risks of fires and explosions through the use of the risk management system of the State University of Bolívar. Once the issue was raised, it was proposed to identify what are the risks of fires produced by pyrotechnics, a plan to prevent fire procedures in the manufacture of pyrotechnics will be carried out. In obtaining information, research strategies were used that allowed us to carry out a direct interview with the personnel who work in the workshops of the association of pyrotechnic artisans San José of the Chimbo canton, prioritizing risks through the characterization of said factors in case of There are fire risks that have been interpreted each of them. Among the main risks of pyrotechnic fires, the most affected were fire due to the manufacture of gunpowder, preparation of the thunder of the flyer, combining chemical substances, elaboration of bright lights, colored sparklers, spinners with magnesium and the cutting of the wick that it they do manually.